Endoplasmic reticulum‐associated degradation mediated by MoHrd1 and MoDer1 is pivotal for appressorium development and pathogenicity of Magnaporthe oryzae. (8th June 2020) - Tang, Wei; Jiang, Haolang; Aron, Osakina; Wang, Min; Wang, Xueyu; Chen, Jiangfeng; Lin, Birong; Chen, Xuehang; Zheng, Qiaojia; Gao, Xiuqin; He, Dou; Wang, Airong; et al.
Summary: Most secretory proteins are folded and modified in the endoplasmic reticulum (ER); however, protein folding is error‐prone, resulting in toxic protein aggregation and cause ER stress. Irreversibly misfolded proteins are subjected to ER‐associated degradation (ERAD), modified by ubiquitination, and degraded by the 26S proteasome. The yeast ERAD ubiquitin ligase Hrd1p and multispanning membrane protein Der1p are involved in ubiquitination and transportation of the folding‐defective proteins. Here, we performed functional characterization of MoHrd1 and MoDer1 and revealed that both of them are localized to the ER and are pivotal for ERAD substrate degradation and the ER stress response. MoHrd1 and MoDer1 are involved in hyphal growth, asexual reproduction, infection‐related morphogenesis, protein secretion and pathogenicity of M. oryzae . Importantly, MoHrd1 and MoDer1 mediated conidial autophagic cell death and subsequent septin ring assembly at the appressorium pore, leading to abnormal appressorium development and loss of pathogenicity. In addition, deletion of MoHrd1 and MoDer1 activated the basal unfolded protein response (UPR) and autophagy, suggesting that crosstalk between ERAD and two other closely related mechanisms in ER quality control system (UPR and autophagy) governs the ER stress response. Our study indicates the importance of ERAD function in fungal development and pathogenesis of M. oryzae .